G486(P) First successful paediatric hla incompatible renal transplantation in the united kingdom. (27th April 2015) - Marks, SD; Riordan, M; Boyle, S; Bradley, S; Knapp, K; Vaughan, R; Shaw, O; Wright, E; Mamode, N
Abstract : Aims: To report the successful outcome of HLA incompatible renal transplantation using plasmapheresis and intravenous immunoglobulin (on day –1) and quadruple immunosuppression with anti–thymocyte globulin (1.5 mg/kg day 1–4), corticosteroids, mycophenolate mofetil and tacrolimus (from day -7). Methods: Six month follow–up data of 14–year old young lady who underwent living related ABO compatible (O into B) and HLA incompatible renal transplantation from her father (mismatch 0, 1, 1) for end-stage kidney disease on peritoneal dialysis secondary to congenital abnormalities of the kidney and urinary tract with bilateral renal dysplasia, recurrent urinary tract infections, bilateral vesico–ureteric reflux after left ureteric reimplantation and right nephrectomy. She had a previous failed renal transplantation at 11 years of age with primary non–function due to intra-renal thrombosis (no acute rejection or TMA) requiring transplant nephrectomy the day after transplantation with 95–100% calculated reaction frequency due to HLA antibodies, specific for mismatches HLA B7 and DQ8 against father with B cell positive (T cell negative) crossmatch which was reduced to negative with test plasma exchange and reduction in MFI from 16, 200 to 6, 480 and from 11, 602 to 4, 625 on the day prior to transplantation. She had no offers from the deceased donor waiting list or via the paired exchange scheme (NLDKSS). Results: Successful renal transplant without further antibody removal or surgical complications with six month follow–up data with stable renal allograft function with eGFR of 60–96 mls/min/1.73m 2, 12-hour trough tacrolimus and mycophenolate levels of 7.3 mcg/l and 3.0 mg/l respectively, controlled hypertension on one anti-hypertensive agent with minimal albuminuria (17.4 mg/mmol). Her DSA reduced to 4, 691on day 2 but increased further to 23, 772 to 38, 630 during weeks 1 to 3 and have stabilised out at 21, 246 to 22, 168 (B7 and DQ8 of 8, 407 and 13, 761 respectively). She has had three percutaneous renal transplant biopsies at weeks 2, 7 and 11 without acute rejection or IFTA but moderate concentric fibrous intimal thickening of large muscular arteries and C4d deposition in peritubular capillaries and glomeruli. Conclusions: This is the first paediatric HLA incompatible renal transplantation in UK and highlights that clinicians must consider this option in ESKD patients whose living donors have been excluded due to HLA incompatibility.